Growth and characterization of InGaN thin films on Si (111) substrate by RF magnetron sputtering: N2 gas flow effect - Erdoğan, Erman; Kundakci, Mutlu; Kasapoglu, Ahmet Emre; Gur, Emre (AMER INST PHYSICS, 2018)
In this study, effect of N-2 gas flow rates on structural, optical and morphological properties of InGaN thin films grown by Radio Frequency Magnetron Sputtering (RFMS) method on n-type silicon (111) substrate have been investigated. X-ray diffraction (XRD) measurements confirmed that InGaN thin films have been successfully deposited and exhibited diffraction peak belong to (002) plane for each film. The surface roughness of InGaN thin films has been determined by using Atomic Force Microscopy (AFM). The energy band gap of the film was determined by using the optical absorption spectra around 2.49 and 2.47 eV for each film.
33rd International Physics Congress of the Turkish-Physical-Society (TPS) -- SEP 06-10, 2017 -- Bodrum, TURKEY